Ответ:
(9 - 1 - 5) • 2 = 3 • 2 = 6 ✓
9 • 1 - 5 + 2 = 9 - 5 + 2 = 6 ✓
1. 9 : 1 - 5 + 2 = 6
2. 9 * 1 - 5 + 2 = 6
3. (9 - 1 - 5) * 2 = 6
Пошаговое объяснение:
1. 9 : 1 - 5 + 2 = 9 - 5 + 2 = 4 + 2 = 6
2. 9 * 1 - 5 + 2 = 9 - 5 + 2 = 4 + 2 = 6
3. (9 - 1 - 5) * 2 = 3 * 2 = 6
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
(9 - 1 - 5) • 2 = 3 • 2 = 6 ✓
9 • 1 - 5 + 2 = 9 - 5 + 2 = 6 ✓
Ответ:
1. 9 : 1 - 5 + 2 = 6
2. 9 * 1 - 5 + 2 = 6
3. (9 - 1 - 5) * 2 = 6
Пошаговое объяснение:
1. 9 : 1 - 5 + 2 = 9 - 5 + 2 = 4 + 2 = 6
2. 9 * 1 - 5 + 2 = 9 - 5 + 2 = 4 + 2 = 6
3. (9 - 1 - 5) * 2 = 3 * 2 = 6